Give what is due: the need to prioritize healthcare workers in response to COVID-19 pandemic - Punsalan, Mairre Louie D (J Public Health (Oxf), 2021)
In a recent correspondence published in this journal, the need to prioritize healthcare workers by the government must be considered. Various negative effects were seen from non-prioritization of healthcare workers. With this, healthcare workers heed distress calls affecting their physical and mental well-being. If prioritization is given and initiatives are done, the needs of healthcare workers will be sufficed so that they will be working at maximum to mitigate the spread of COVID-19.